Silicon-carbon composite material, preparation method thereof, and secondary battery

By using silicon-carbon skeletons, nano-silicon deposition and carbon cladding design in silicon-carbon composite materials, the problems of silicon carbide generation and silicon grain growth in high temperature processes in the prior art are solved. Silicon-carbon composite materials with high capacity, good cycle and rate performance are achieved.

CN117790730BActive Publication Date: 2025-02-07GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311792492.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-02-07
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials are prone to generate silicon carbide and silicon grains during high-temperature vapor deposition and carbon coating, resulting in sharp reduction in capacity and poor performance, and the preparation process is complex and costly.

Method used

Using a silicon carbon framework composed of crystalline silicon and carbon materials, a novel silicon carbon composite material is formed through nano-silicon deposition and carbon cladding design to avoid silicon carbide generation and silicon grain growth during high temperatures. Large, while improving the structural stability and electrochemical properties of the material.

Benefits of technology

The high capacity, good cycle performance and rate performance of silicon-carbon composite materials are achieved, while simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117790730B_ABST
    Figure CN117790730B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of material preparation, and provides a silicon-carbon composite material, a preparation method thereof, and a secondary battery. The silicon-carbon composite material comprises a silicon-carbon core and a carbon coating layer coating the silicon-carbon core. The silicon-carbon core comprises a silicon-carbon matrix and nano-silicon. The silicon-carbon matrix comprises a silicon-carbon skeleton composited with crystalline silicon and carbon material and a plurality of holes penetrating the interior of the silicon-carbon skeleton, wherein nano-silicon is accommodated in the plurality of holes. The prepared silicon-carbon composite material has a novel silicon-carbon matrix, which can avoid the formation of silicon carbide and the growth of silicon grains during high-temperature gas-phase silicon deposition and high-temperature carbon coating. At the same time, the silicon-carbon composite material has a stable structure, a high capacity, and better cycle and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a silicon-carbon composite material and a preparation method thereof, and a secondary battery. Background Art

[0002] With the development of society, people have higher and higher requirements for energy conversion and storage technology. Compared with traditional secondary batteries such as lead-acid batteries and nickel-cadmium batteries, lithium-ion batteries have the advantages of high energy density, long cycle life, high operating voltage, and low self-discharge rate. They have been widely used in the field of portable electronic products and have also shown great potential in the fields of electric vehicles and grid energy storage. However, the energy density of commercial lithium-ion batteries with graphite as the negative electrode is close to the theoretical limit and cannot meet the energy needs of electric vehicles. Therefore, the development of new electrode materials with high capacity and high stability is the current research focus.

[0003] Silicon has an extremely high theoretical lithium storage capacity (4200mAh / g), a moderate reaction potential and abundant reserves, and is one of the most promising negative electrode materials. However, the severe volume expansion and contraction of silicon during lithium insertion and removal can easily lead to silicon particle pulverization, electrode structure collapse, and solid-liquid interface film instability, and ultimately cause electrode material failure. The use of nano-sized silicon can reduce the absolute volume change of the material during charging and discharging, and the composite of silicon and carbon can alleviate volume expansion and enhance electrochemical stability. Therefore, nano-sizing of silicon and silicon-carbon composite are the main research directions for solving the above problems.

[0004] At present, the composite methods of nano-silicon and carbon mainly include: (1) using grinding equipment to grind silicon to nano-size, and using different carbon sources or carbon coating processes to composite nano-silicon and carbon to obtain silicon-carbon composite materials. However, this method has problems such as poor dispersion of nano-silicon, limited expansion improvement, and low upper capacity limit; (2) using chemical vapor deposition process to high-temperature crack the gaseous silicon source to obtain a silicon-carbon composite material in which nano-silicon is deposited in the pores of porous carbon. This method has the characteristics of simple process and high capacity. However, when porous carbon is used as the skeleton, silicon carbide or silicon grain growth is easily generated when the reaction temperature is too high, resulting in a sharp decrease in capacity, and the process temperature is greatly limited. In addition, when porous carbon is used as the skeleton to deposit silicon, all silicon filled in the skeleton pores requires pores to accommodate, so the required skeleton pore volume requirements are relatively high. For example, to deposit silicon with a content of more than 50wt.%, the required pore volume is greater than 0.8cm 3 / g. On the one hand, a larger skeleton pore volume will make the skeleton preparation process complicated and increase the cost. On the other hand, the skeleton structure is unstable under large pore volume, which is not conducive to the cyclic stability of the material. When the reaction temperature is too high during vapor deposition or carbon coating, the porous carbon skeleton with large pore volume is easy to react with the deposited nano-silicon to generate silicon carbide, resulting in a sharp decrease in capacity and poor performance.

[0005] Therefore, how to design a silicon-carbon composite material to reduce the volume expansion of silicon, improve the cycle performance, and have a simple preparation process and low cost is of great significance to the application of silicon-based materials in lithium-ion batteries. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide a silicon-carbon composite material and a preparation method thereof, and a secondary battery. The prepared silicon-carbon composite material has a novel silicon-carbon matrix, which can avoid the formation of silicon carbide and the growth of silicon grains during high-temperature gas phase silicon deposition and high-temperature carbon coating. At the same time, the silicon-carbon composite material has a stable structure, high capacity and better cycle and rate performance.

[0007] To achieve the above object, the first aspect of the present invention provides a silicon-carbon composite material, comprising a silicon-carbon core and a carbon coating layer covering the silicon-carbon core. The silicon-carbon core comprises a silicon-carbon matrix and nano-silicon. The silicon-carbon matrix comprises a silicon-carbon skeleton composited with crystalline silicon and carbon material and a plurality of holes penetrating the interior of the silicon-carbon skeleton, wherein the nano-silicon is accommodated in the plurality of holes.

[0008] The silicon-carbon composite material of the present invention has at least the following technical effects.

[0009] (1) The silicon material includes crystalline silicon located in the silicon-carbon skeleton itself and nano-silicon contained in the pores of the silicon-carbon matrix. Therefore, compared with the carbon skeleton with the same silicon content, the silicon-carbon composite material of the present invention has a lower requirement for the pore volume of the silicon-carbon matrix and does not require a larger pore volume to accommodate the silicon material. Therefore, the structural stability of the material is higher, which is beneficial to improving the electrochemical properties of the material and can obtain a higher reversible specific capacity at a relatively low silicon deposition amount.

[0010] (2) The silicon in the silicon-carbon skeleton itself is crystalline silicon. The crystalline silicon and the carbon material in the silicon-carbon skeleton are carbonized at high temperature to form a composite, which has a strong binding force and can prevent the formation of silicon carbide in the subsequent vapor deposition process. On the other hand, the heat absorption characteristics of crystalline silicon can prevent the subsequent deposited nanosilicon from transforming into crystalline silicon during the carbon coating process.

[0011] (3) Crystalline silicon and carbon materials are compositely distributed in the silicon-carbon skeleton, and nano-silicon is contained in the pores of the silicon-carbon matrix, which can achieve uniform distribution of silicon materials in the silicon-carbon composite material. At the same time, the existence of pores also provides reserved space for the volume expansion of silicon materials, greatly improving the cyclic performance of the material.

[0012] (4) The carbon coating layer covering the silicon-carbon core can reduce the specific surface area of ​​the silicon-carbon composite material, avoid side reactions caused by direct contact between silicon and the electrolyte, and greatly enhance the high-temperature processing performance of the silicon-carbon composite material.

[0013] In some embodiments, the tap density of the silicon-carbon composite material is 0.6 g / cm 3Up to 1.5g / cm 3 .

[0014] In some embodiments, the true density of the silicon-carbon composite material is 1.5 g / cm 3 Up to 2.0g / cm 3 .

[0015] In some embodiments, the pore volume of the silicon-carbon composite material is 0.001 cm 3 / g to 0.100cm 3 / g.

[0016] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is 1 m 2 / g to 10m 2 / g.

[0017] In some embodiments, the silicon-carbon composite material has a median particle size of 1 μm to 50 μm.

[0018] In some embodiments, the silicon-carbon composite material has a silicon content of 30% to 75% by mass.

[0019] In some embodiments, the true density of the silicon carbon matrix is ​​1.5 g / cm 3 Up to 2.4g / cm 3 .

[0020] In some embodiments, the pore volume of the silicon carbon matrix is ​​0.1 cm 3 / g to 0.8cm 3 / g.

[0021] In some embodiments, the ratio of the pore volume of the silicon carbon matrix with a pore diameter of 1 nm to 10 nm to the total pore volume is P, and 0.4≤P≤0.8.

[0022] In some embodiments, the specific surface area of ​​the silicon carbon matrix is ​​200 m 2 / g to 1800m 2 / g.

[0023] In some embodiments, the silicon carbon substrate has a Dv50 of 1 μm to 40 μm.

[0024] In some embodiments, the average pore size of the pores is from 1 nm to 100 nm.

[0025] In some embodiments, the pores include at least one of micropores, mesopores, and macropores.

[0026] In some embodiments, the Dv50 of the crystalline silicon is from 50 nm to 120 nm.

[0027] In some embodiments, the particle size distribution dispersion of the crystalline silicon is σ, 0<σ≤1.0, σ=(Dv90-Dv10) / Dv50.

[0028] In some embodiments, crystalline silicon comprises 10% to 60% by mass of the silicon carbon matrix.

[0029] In some embodiments, the carbon material includes soft carbon and / or hard carbon.

[0030] In some embodiments, the nano-silicon is amorphous silicon, and the grain size of the amorphous silicon is ≤3 nm.

[0031] In some embodiments, the mass ratio of nano-silicon to crystalline silicon is R, 0.2≤R≤20.0.

[0032] In some embodiments, nano-silicon accounts for 10% to 75% of the total mass of the silicon-carbon composite material.

[0033] In some embodiments, nano-silicon is also distributed on the surface of the silicon carbon matrix.

[0034] In some embodiments, the distribution uniformity of nano-silicon and crystalline silicon is α1 / α2, 0.67≤α1 / α2≤1.50.

[0035] In some embodiments, the carbon coating layer has a thickness of 2 nm to 200 nm.

[0036] In some embodiments, the carbon coating layer is 1% to 15% by weight of the silicon-carbon composite material.

[0037] In some embodiments, the carbon coating includes crystalline carbon and / or amorphous carbon.

[0038] A second aspect of the present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps.

[0039] (I) Preparation of silicon carbon matrix

[0040] Crystalline silicon, a first carbon source, a pore-forming agent and a dispersant are mixed in a solvent to obtain a slurry, and the slurry is dried and then carbonized to obtain a silicon-carbon matrix. The pore-forming agent forms pores in the silicon-carbon matrix after carbonization, and the ratio of the pore volume of the silicon-carbon matrix with a pore diameter of 1nm to 10nm to the total pore volume is P, 0.4≤P≤0.8, and the Dv50 of the crystalline silicon is 50nm to 120nm.

[0041] (II) Nano-silicon deposition

[0042] Nano-silicon is deposited on the silicon-carbon matrix so that the nano-silicon is at least deposited in the pores to obtain a silicon-carbon core, and the mass ratio of the nano-silicon to the crystalline silicon in the silicon-carbon core is R, 0.2≤R≤20.0.

[0043] (III) Carbon coating

[0044] The silicon carbon core is carbon coated with a second carbon source.

[0045] In the preparation method of the silicon-carbon composite material of the present invention, crystalline silicon, a first carbon source, a pore-forming agent and a dispersant are mixed in a solvent to obtain a slurry, and a dispersant is used for dispersion, so that the crystalline silicon and the pore-forming agent can be evenly dispersed in the system. After drying and carbonization, crystalline silicon and a silicon-carbon matrix with uniform pore distribution can be obtained. Then, nano-silicon is deposited in the pores of the silicon-carbon matrix, which avoids the situation that the porous carbon skeleton is used as the matrix, and the structure is unstable when the pore volume is too large or silicon carbide is generated at high temperature, which greatly improves the reversible specific capacity and the first coulomb efficiency of the material. At the same time, the deposition of nano-silicon in the pores of the silicon-carbon matrix and the uniform distribution of crystalline silicon can effectively reduce the volume expansion of silicon, and further improve the electrochemical performance and cycle performance of the material. The preparation method of the silicon-carbon composite material of the present invention has a simple process, does not require an activation process, and has low requirements on equipment and preparation process.

[0046] In conjunction with the second aspect, the silicon-carbon composite material comprises a silicon-carbon core and a carbon coating layer. Optionally, the carbon coating layer can be one layer, two layers, three layers, and so on.

[0047] In some embodiments, depositing nano-silicon on a silicon-carbon substrate includes introducing a gaseous silicon source into a reactor containing a silicon-carbon substrate under a protective gas to perform vapor deposition.

[0048] In some embodiments, the protective gas includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0049] In some embodiments, the gaseous silicon source is obtained by heating a silicon source material at 40° C. to 200° C., the silicon source material is in liquid phase and includes at least one of trisilane, butadisilane, trichlorosilane, methyltrichlorosilane and dimethyldichlorosilane.

[0050] In some embodiments, the gaseous silicon source is at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.

[0051] In some embodiments, the concentration of the gaseous silicon source is between 5% and 50% by volume.

[0052] In some embodiments, the vapor deposition temperature is 400° C. to 700° C., and the time is 1 h to 12 h.

[0053] In some embodiments, the particle size distribution dispersion of the crystalline silicon is σ, 0<σ≤1.0, σ=(Dv90-Dv10) / Dv50.

[0054] In some embodiments, the first carbon source includes at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin and citric acid.

[0055] In some embodiments, the pore former includes at least one of ammonium carbonate, ammonium bicarbonate, magnesium carbonate, magnesium bicarbonate, ammonium oxalate, ammonium phosphate, diammonium hydrogen phosphate, and ammonium nitrate.

[0056] In some embodiments, the dispersant includes at least one of sodium lauryl sulfate, polyacrylamide, polyethylene glycol fatty acid esters, polyvinyl pyrrolidone, stearic acid monoglyceride, and polyethylene glycol.

[0057] In some embodiments, the solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane, and cyclohexane.

[0058] In some embodiments, the mass ratio of crystalline silicon, the first carbon source, the pore former, the dispersant, and the solvent is 1:0.2-15.0:0.05-0.50:0.03-0.30:1-30.

[0059] In some embodiments, the mixing is grinding mixing, ball milling mixing or VC mixing. The mixing time is 1 hour to 5 hours. The mixing speed is 500 rpm to 2500 rpm.

[0060] In some embodiments, the drying is spray drying, the feed inlet temperature of the spray drying is 150°C to 280°C, and the discharge outlet temperature of the spray drying is 70°C to 150°C.

[0061] In some embodiments, the carbonization is performed in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0062] In some embodiments, the carbonization temperature is 600° C. to 1000° C. The carbonization time is 1 h to 10 h.

[0063] In some embodiments, carbon coating includes mixing the silicon carbon core and a second carbon source and subjecting the mixture to a high temperature heat treatment under a protective gas.

[0064] In some embodiments, the protective gas includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0065] In some embodiments, the second carbon source is at least one of a gas-phase carbon source, a liquid-phase carbon source, and a solid-phase carbon source.

[0066] In some embodiments, the second carbon source is a gaseous carbon source, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene and acetylene.

[0067] In some embodiments, the second carbon source is a gas-phase carbon source, and the step of mixing the gas-phase carbon source and the silicon-carbon core includes: heating the silicon-carbon core and then introducing the gas-phase carbon source.

[0068] The second carbon source is a gaseous carbon source, and the volume concentration of the gaseous carbon source is 5% to 50%.

[0069] The second carbon source is a liquid carbon source, and the liquid carbon source is at least one of n-hexane, cyclohexane, isoheptane, acetone, butanone, cyclohexanone, benzene, toluene, xylene, styrene, phenol, methyl acetate, ethyl acetate, propyl acetate and liquefied petroleum gas.

[0070] In some embodiments, the second carbon source is a liquid carbon source, and the mass ratio of the liquid carbon source to the silicon carbon core is 1:2-50.

[0071] In some embodiments, the second carbon source is a solid carbon source, and the solid carbon source includes at least one of asphalt, phenolic resin, epoxy resin, polyvinyl alcohol, polypyrrole, polyaniline, polydopamine, sucrose, glucose, citric acid and lignin.

[0072] In some embodiments, the second carbon source is a solid carbon source, and the mass ratio of the solid carbon source to the silicon carbon core is 1:2-50.

[0073] In some embodiments, the heat treatment is performed at a temperature of 600° C. to 900° C. for a time of 1 h to 12 h.

[0074] In some embodiments, the heat treatment is followed by sequential disintegration, screening and demagnetization treatments.

[0075] The present invention also provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte. The negative electrode material is the aforementioned silicon-carbon composite material or a silicon-carbon composite material prepared by the aforementioned method for preparing the silicon-carbon composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 It is a schematic diagram of the structure of the silicon-carbon composite material of the present invention.

[0077] Figure 2 Schematic diagram of the structure of the silicon carbon matrix of the present invention.

[0078] Figure 3 This is the XRD spectrum of the silicon-carbon composite material of Example 1.

[0079] Figure 4 This is the XRD spectrum of the silicon-carbon composite material of Comparative Example 4.

[0080] Figure 5 This is the XRD spectrum of the silicon-carbon composite material of Comparative Example 5. DETAILED DESCRIPTION

[0081] The silicon-carbon composite material of the present invention can be used alone or mixed with other negative electrode active materials (such as natural graphite, artificial graphite, soft carbon and / or hard carbon, etc.). The silicon-carbon composite material can be used as a negative electrode active material in a secondary battery. The secondary battery includes a positive electrode material and a negative electrode material. The positive electrode material includes at least one of a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material, a nickel cobalt manganese oxide positive electrode material, and a nickel cobalt aluminum oxide positive electrode material.

[0082] The first reversible specific capacity of the silicon-carbon composite material is ≥2000mAh / g, which can be but not limited to

[0083] ≥2200mAh / g, ≥2220mAh / g, ≥2240mAh / g≥2260mAh / g, ≥2280mAh / g,

[0084] ≥2300mAh / g, ≥2320mAh / g, ≥2340mAh / g≥2360mAh / g, ≥2380mAh / g,

[0085] ≥2400mAh / g. The first coulombic efficiency of the silicon-carbon composite material is ≥90.0%, which can be but not limited to

[0086] ≥90.0%, ≥90.2%, ≥90.4%, ≥90.6%, ≥90.8%, ≥91.0%, ≥91.2%, ≥91.4%,

[0087] ≥91.6%, ≥91.8%, ≥92.0%, ≥92.2%, ≥92.4%, ≥92.6%, ≥92.8%, ≥93.0%. The 300-week capacity retention rate of the silicon-carbon composite material is ≥87.0%, which can be, but is not limited to, ≥87.0%, ≥88.%,

[0088] ≥89.0%, ≥90.0%, ≥91.0%, ≥92.0%, ≥93.0%. 2C / 0.1C capacity retention rate ≥88.%, can be but not limited to ≥88.0%, ≥89.0%, ≥90.0%, ≥91.0%, ≥92.0%, ≥93.0%, ≥94.0%,

[0089] ≥94.5%.

[0090] The tap density of silicon-carbon composite material is 0.6g / cm 3 Up to 1.5g / cm 3 , can be but not limited to 0.6g / cm 3, 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 The true density of silicon-carbon composite material is 1.5g / cm 3 Up to 2.0g / cm 3 , can be but not limited to 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 The pore volume of the silicon-carbon composite material is 0.001 cm 3 / g to 0.100cm 3 / g, can be but not limited to 0.001cm 3 / g, 0.005cm 3 / g, 0.010cm 3 / g, 0.020cm 3 / g, 0.030cm 3 / g, 0.040cm 3 / g, 0.050cm 3 / g, 0.060cm 3 / g, 0.070cm 3 / g, 0.080cm 3 / g, 0.090cm 3 / g, 0.100cm 3 / g. The specific surface area of ​​silicon-carbon composite material is 1m 2 / g to 10m 2 / g, can be but not limited to 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g. The median particle size of the silicon-carbon composite material is 1 μm to 50 μm, and may be, but not limited to, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm. The mass content of silicon in the silicon-carbon composite material is 30% to 75%, and may be, but not limited to, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%.

[0091] The silicon-carbon composite material of the present invention can be used Figure 1 and Figure 2 An example is given below. Figure 1 As shown, the silicon-carbon composite material 100 includes a silicon-carbon core 10 and a carbon coating layer 30 coating the silicon-carbon core 10 .

[0092] Further Figure 1 and 2 As shown, the silicon carbon core 10 includes a silicon carbon matrix 11 and nano silicon 13. The silicon carbon matrix 11 includes a silicon carbon skeleton 11a composed of crystalline silicon 111 and carbon material 113 and a plurality of holes 11b penetrating the silicon carbon skeleton 11a, and the nano silicon 13 is accommodated in the plurality of holes 11b.

[0093] Among them, the true density of the silicon carbon matrix is ​​1.5g / cm 3 Up to 2.4g / cm 3 , can be but not limited to 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 The pore volume of the silicon carbon matrix is ​​0.1 cm 3 / g to 0.8cm 3 / g, can be but not limited to 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g. The ratio of the pore volume of the silicon-carbon matrix with a pore size of 1nm to 10nm to the total pore volume is P, 0.4≤P≤0.8. Under this ratio, nano-silicon and crystalline silicon are evenly distributed, which is conducive to the improvement of cycle and rate performance. The specific surface area of ​​the silicon-carbon matrix is ​​200m 2 / g to 1800m 2 / g, can be but not limited to 200m 2 / g, 400m 2 / g、600m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 The Dv50 of the silicon carbon matrix is ​​1 μm to 40 μm, and may be, but is not limited to, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm.

[0094] The multiple holes penetrating the interior of the silicon-carbon skeleton may be connected or not connected, and the multiple holes are uniformly dispersed in the silicon-carbon matrix. At least some of the holes have at least one opening facing outward so that nano-silicon enters the hole through the opening, and the average pore size of the opening hole is 1nm to 100nm, which can be but not limited to 1nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. The pores include at least one of micropores, mesopores and macropores.

[0095] In addition, the carbon material includes soft carbon and / or hard carbon. The Dv50 of crystalline silicon is 50nm to 120nm, which can be but not limited to 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm. The particle size distribution dispersion of crystalline silicon is σ, 0<σ≤1.0, which can be but not limited to 0<σ≤0.8 or 0<σ≤0.5 or 0<σ≤0.3 or 0<σ≤0.1, σ=(Dv90-Dv10) / Dv50, Dv90, Dv10, Dv50 are all the particle sizes of crystalline silicon. Crystalline silicon accounts for 10% to 60% of the mass of the silicon-carbon matrix, which can be but not limited to 10%, 20%, 30%, 40%, 50%, 60%. Nano silicon is amorphous silicon, and the grain size of amorphous silicon is ≤3nm, which can be but not limited to ≤2nm, or ≤1nm. Nano silicon accounts for 10% to 75% of the total mass of the silicon-carbon composite material, which may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%. When deposited, nano silicon is distributed not only in the pores of the silicon-carbon matrix, but also on the surface of the silicon-carbon matrix.

[0096] The mass ratio of nano silicon and crystalline silicon is R, 0.2≤R≤20.0, and can be but not limited to 0.2, 0.6, 1.0, 2.0, 3.0, 5.0, 7.0, 9.0, 10.0, 12.0, 14.0, 16.0, 18.0, 20.0. When R is set within a certain range, the silicon-carbon composite material has good electrochemical performance. When R<0.2, the content of nano silicon deposited by vapor phase is less, the content of crystalline silicon is higher, and the efficiency of the silicon-carbon composite material is lower, thereby affecting the cycle performance. When the R value>20, there is more nano silicon deposited by chemical vapor phase, and less crystalline silicon in the porous silicon-carbon skeleton. It is impossible to ensure that the nano silicon can maintain the amorphous phase and no silicon carbide is generated after vapor phase deposition or high-temperature carbon coating, thereby reducing the impact on the efficiency and cycle performance of the silicon-carbon composite material.

[0097] The distribution uniformity of nano-silicon and crystalline silicon is α1 / α2, 0.67≤α1 / α2≤1.50, and can be, but not limited to, 0.67, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50. The closer α1 / α2 is to 1, the more uniform the distribution of nano-silicon particles and crystalline silicon particles is, indicating that the composite of crystalline silicon with carbon material in the silicon-carbon matrix and the deposition of nano-silicon in the skeleton pores achieve uniform distribution of silicon in the silicon-carbon composite material.

[0098] The carbon coating layer may be a carbon layer such as one layer, two layers, or three layers formed by carbon coating. In some embodiments, the thickness of the carbon coating layer is 2nm to 200nm, and may be, but not limited to, 2nm, 5nm, 10nm, 20nm, 50nm, 100nm, 150nm, or 200nm. The carbon coating layer is 1% to 15% of the mass of the silicon-carbon composite material, and may be, but not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%. The carbon coating layer includes crystalline carbon and / or amorphous carbon.

[0099] The method for preparing the silicon-carbon composite material of the present invention may include the following steps: (I) preparing a silicon-carbon matrix; (II) depositing nano-silicon; and (III) carbon coating.

[0100] Step (I) of preparing the silicon-carbon matrix comprises mixing crystalline silicon, a first carbon source, a pore-forming agent and a dispersant in a solvent to obtain a slurry, and then drying the slurry and carbonizing it to obtain the silicon-carbon matrix.

[0101] Wherein, the particle size distribution dispersion σ of crystalline silicon, 0<σ≤1.0, can be but not limited to 0<σ≤0.8 or 0<σ≤0.5 or 0<σ≤0.3 or 0<σ≤0.1, σ=(Dv90-Dv10) / Dv50. The Dv50 of crystalline silicon is 50nm to 120nm, can be but not limited to 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, and the Dv50 of crystalline silicon should not be too large, otherwise it will cause large expansion and affect the structural stability of the silicon-carbon matrix. The first carbon source includes at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin and citric acid. The pore-forming agent includes at least one of ammonium carbonate, ammonium bicarbonate, magnesium carbonate, magnesium bicarbonate, ammonium oxalate, ammonium phosphate, diammonium hydrogen phosphate and ammonium nitrate. After carbonization, the pore-forming agent forms pores in the silicon-carbon matrix, and the ratio of the pore volume of the silicon-carbon matrix with a pore diameter of 1nm to 10nm to the total pore volume is P, 0.4≤P≤0.8. The content of the pore-forming agent should not be too low, otherwise it will not be possible to form enough pores to accommodate nano-silicon. Similarly, the content of the pore-forming agent should not be too high, otherwise it will lead to a lower pore volume with a pore diameter of 1nm to 10nm, that is, the P value is outside the range of 0.4 to 0.8, and subsequent nano-silicon deposition will cause uneven distribution of nano-silicon and crystalline silicon due to concentrated accumulation. The dispersant includes at least one of sodium dodecyl sulfate, polyacrylamide, fatty acid polyethylene glycol ester, polyvinyl pyrrolidone, stearic acid monoglyceride and polyethylene glycol. The solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane and cyclohexane. The mass ratio of crystalline silicon, the first carbon source, the pore-forming agent, the dispersant and the solvent is 1:0.2-15.0:0.05-0.50:0.03-0.30:1-30, and can be but is not limited to 1:5.0:0.10:0.10:5, 1:10.0:0.20:0.20:10, 1:3.0:0.30:0.120:15, 1:5.0:0.30:0.30:10, 1:10.0:0.40:0.20:25, 1:15.0:0.25:0.15:20, 1:1.0:0.25:0.15:18, 1:3.0:0.30:0.30:8, 1:2.5:0.20:0.15:25.

[0102] Mixing is grinding mixing, ball milling mixing or VC mixing. The mixing time is 1h to 5h, which can be but not limited to 1h, 2h, 3h, 4h, 5h. The mixing speed is 500rpm to 2500rpm, which can be but not limited to 500rpm, 700rpm, 900rpm, 1000rpm, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm, 2500rpm. Drying is spray drying, and the feed inlet temperature of spray drying is 150℃ to 280℃, which can be but not limited to 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃. The discharge port temperature is 70°C to 150°C, and may be, but not limited to, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C. Carbonization is carried out in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton, and xenon. The carbonization temperature is 600°C to 1000°C, and may be, but not limited to, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, and 1000°C. The carbonization time is 1h to 10h, and may be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h.

[0103] Step (II) of nano-silicon deposition includes depositing nano-silicon on the silicon-carbon substrate, so that the nano-silicon is at least deposited in the pores to obtain a silicon-carbon core.

[0104] Wherein, the deposition of nano-silicon on the silicon-carbon matrix includes, under protective gas, passing a gaseous silicon source into a reactor with a built-in silicon-carbon matrix for vapor deposition. The protective gas includes at least one of nitrogen, helium, neon, argon, krypton and xenon. The gaseous silicon source is obtained by heating a silicon source material at 40°C to 200°C, the silicon source material is in liquid phase and includes at least one of trisilane, butadisilane, trichlorosilane, methyltrichlorosilane and dimethyldichlorosilane. The heating temperature may be, but is not limited to, 40°C, 50°C, 60°C, 80°C, 100°C, 120°C, 150°C, 200°C. The gaseous silicon source is at least one of monosilane, disilane, monochlorosilane and dichlorosilane. The volume concentration of the gaseous silicon source is 5% to 50%, and may be, but not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%. The temperature of the vapor deposition is 400°C to 700°C, and may be, but not limited to, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C. The time of the vapor deposition is 1h to 12h, and may be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. The mass ratio of nano-silicon and crystalline silicon in the silicon-carbon core obtained after vapor phase silicon deposition is R, 0.2≤R≤20.0, and can be but not limited to 0.2, 0.6, 1.0, 2.0, 3.0, 5.0, 7.0, 9.0, 10.0, 12.0, 14.0, 16.0, 18.0, 20.0. When R is set within a certain range, the silicon-carbon composite material has good electrochemical properties. When R<0.2, the content of nano-silicon deposited by vapor phase is less, the content of crystalline silicon is higher, and the efficiency of the silicon-carbon composite material is lower, thereby affecting the cycle performance. When the R value>20, there is more nano-silicon deposited by chemical vapor phase, and less crystalline silicon in the porous silicon-carbon skeleton. It is impossible to ensure that the nano-silicon can maintain the amorphous phase and the generation of no silicon carbide after vapor phase deposition or high-temperature carbon coating, thereby reducing the impact on the efficiency and cycle performance of the silicon-carbon composite material.

[0105] Step (III) carbon coating includes carbon coating the silicon-carbon core with a second carbon source, and the carbon coating includes mixing the silicon-carbon core and the second carbon source under a protective gas and performing a high-temperature heat treatment. The protective gas includes at least one of nitrogen, helium, neon, argon, krypton and xenon. The second carbon source is at least one of a gas phase carbon source, a liquid phase carbon source and a solid phase carbon source. Corresponding to different second carbon sources, the carbon coating layer may be gas phase coating, solid phase coating or liquid phase coating. Of course, it may also be other coating methods such as plasma, as long as the coating can form a carbon coating layer. The carbon coating layer formed may be one layer, two layers, three layers, and so on. Of course, the silicon-carbon composite material of the present invention is not limited to the method of carbon coating, nor is it limited to the number of layers of the carbon coating layer.

[0106] If the second carbon source is a gaseous carbon source, it is gas-phase coating, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene and acetylene. The silicon-carbon core is heated and then introduced into the gaseous carbon source and subjected to high-temperature heat treatment, and the operation can be carried out in an atmosphere furnace. The volume concentration of the gaseous carbon source is 5% to 50%, which can be but not limited to 5%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%. The temperature of the heat treatment is 600°C to 900°C, which can be but not limited to 600°C, 700°C, 800°C, 900°C. The heating rate is 1°C / min to 10°C / min. As an example, the heating rate can be but not limited to 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, 10°C / min. The heat treatment time is 1 h to 12 h, and can be but is not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h.

[0107] If the second carbon source is a liquid carbon source, it is liquid coating. Liquid coating is to mix the liquid carbon source and the silicon-carbon core evenly under a protective gas and then perform heat treatment to obtain a silicon-carbon composite material. The liquid carbon source is at least one of n-hexane, cyclohexane, isoheptane, acetone, butanone, cyclohexanone, benzene, toluene, xylene, styrene, phenol, methyl acetate, ethyl acetate, propyl acetate and liquefied petroleum gas. The mass ratio of the liquid carbon source to the silicon-carbon core is 1:2 to 50, which can be but not limited to 1:2, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50. The temperature of the heat treatment is 600°C to 900°C, which can be but not limited to 600°C, 700°C, 800°C, 900°C. The heating rate is 1°C / min to 10°C / min. For example, the heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, and 10°C / min. The heat treatment time is 1h to 12h, and may be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.

[0108] If the second carbon source is a solid-phase carbon source, it is solid-phase coating. Solid-phase coating can be to mix the solid-phase carbon source and the silicon-carbon core evenly, and heat-treat under protective gas to obtain a silicon-carbon composite material. The carbon source includes at least one of asphalt, phenolic resin, epoxy resin, polyvinyl alcohol, polypyrrole, polyaniline, polydopamine, sucrose, glucose, citric acid and lignin. The mass ratio of the solid-phase carbon source to the silicon-carbon core is 1:2 to 50, which can be but not limited to 1:2, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50. The temperature of the heat treatment is 600°C to 900°C, which can be but not limited to 600°C, 700°C, 800°C, 900°C. The heating rate is 1°C / min to 10°C / min. For example, the heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, and 10°C / min. The heat treatment time is 1h to 12h, and may be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.

[0109] Further, after the heat treatment, the sintering, screening and demagnetization treatment can be carried out in sequence. The sintering can be, but is not limited to, VC sintering. The rotating speed used during sintering is 500r / min to 3000r / min. As an example, the rotating speed of sintering can be, but is not limited to, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min, 1300r / min, 1400r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min. The sintering time is 30min to 120min. As an example, the sintering time can be, but is not limited to, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min. The screen used for screening is 200 mesh to 800 mesh. As an example, the screen can be, but is not limited to, 200 mesh, 230 mesh, 240 mesh, 250 mesh, 270 mesh, 300 mesh, 325 mesh, 400 mesh, 500 mesh, 600 mesh, and 800 mesh. Demagnetization is performed using a demagnetizer.

[0110] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0111] Example 1

[0112] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0113] (I) Preparation of silicon carbon matrix

[0114] Crystalline silicon (Dv50 is 80nm, weight is 500g), asphalt, ammonium carbonate, sodium dodecyl sulfate and n-hexane are mixed in a mass ratio of 1:3.6:0.3:0.03:10 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray-dried (inlet air temperature is 170℃, outlet air temperature is 80℃), and then carbonized at 750℃ for 5h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix are tested.

[0115] (II) Nano-silicon deposition

[0116] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 500°C under nitrogen protection, introduce monosilane with a volume concentration of 20%, and perform chemical vapor deposition for 3 hours to obtain a silicon-carbon core.

[0117] (III) Carbon coating

[0118] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 700°C at a heating rate of 3°C / min. Acetylene with a volume concentration of 15% was introduced and carbon coating was carried out for 1.5 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0119] The silicon-carbon composite material obtained in Example 1 was subjected to XRD test, and the results are as follows: Figure 3 As shown, it can be seen from the XRD spectrum that there is a diffraction peak at 2θ=28.4°, corresponding to the (111) crystal plane of crystalline silicon, and the amorphous peak within 25°≤2θ≤30° corresponds to amorphous silicon, indicating that the silicon-carbon composite material contains crystalline silicon and amorphous silicon.

[0120] Example 2

[0121] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0122] (I) Preparation of silicon carbon matrix

[0123] Crystalline silicon (Dv50 is 80nm, weight is 500g), asphalt, ammonium carbonate, sodium dodecyl sulfate and n-hexane are mixed in a mass ratio of 1:3.6:0.2:0.03:10 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray-dried (inlet air temperature is 170℃, outlet air temperature is 80℃), and then carbonized at 750℃ for 5h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix are tested.

[0124] (II) Nano-silicon deposition

[0125] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 500°C under nitrogen protection, introduce monosilane with a volume concentration of 15%, and perform chemical vapor deposition for 3.5 hours to obtain a silicon-carbon core.

[0126] (III) Carbon coating

[0127] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 700°C at a heating rate of 3°C / min. Acetylene with a volume concentration of 15% was introduced and carbon coating was carried out for 1.5 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0128] Example 3

[0129] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0130] (I) Preparation of silicon carbon matrix

[0131] Crystalline silicon (Dv50 is 80nm, weight is 500g), asphalt, ammonium bicarbonate, sodium dodecyl sulfate and n-hexane are mixed in a mass ratio of 1:3.6:0.24:0.03:10 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray dried (inlet air temperature is 170℃, outlet air temperature is 80℃), and then carbonized at 750℃ for 5h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix are tested.

[0132] (II) Nano-silicon deposition

[0133] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 530° C. under nitrogen protection. Monosilane with a volume concentration of 15% was introduced, and chemical vapor deposition was performed for 3.5 hours to obtain a silicon-carbon core.

[0134] (III) Carbon coating

[0135] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 750°C at a heating rate of 3°C / min. Ethylene with a volume concentration of 20% was introduced and carbon coating was carried out for 2.0 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0136] Example 4

[0137] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0138] (I) Preparation of silicon carbon matrix

[0139] Crystalline silicon (Dv50 of 80 nm and weight of 500 g), asphalt, ammonium bicarbonate, sodium dodecyl sulfate and xylene were mixed in a mass ratio of 1:12:0.4:0.05:21 for VC mixing for 2 h at a mixing speed of 1500 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 200°C and outlet air temperature of 140°C) and carbonized at 800°C for 4 h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix were tested.

[0140] (II) Nano-silicon deposition

[0141] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 530° C. under nitrogen protection. Monosilane with a volume concentration of 20% was introduced, and chemical vapor deposition was performed for 6 hours to obtain a silicon-carbon core.

[0142] (III) Carbon coating

[0143] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 750°C at a heating rate of 3°C / min. Ethylene with a volume concentration of 20% was introduced and carbon coating was carried out for 1.5 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0144] Example 5

[0145] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0146] (I) Preparation of silicon carbon matrix

[0147] Crystalline silicon (Dv50 of 100 nm and weight of 500 g), asphalt, ammonium bicarbonate, sodium dodecyl sulfate and xylene were mixed in a mass ratio of 1:2.0:0.2:0.05:12 for VC mixing for 3 hours at a mixing speed of 1800 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 200°C and outlet air temperature of 140°C) and carbonized at 800°C for 4 hours in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix were tested.

[0148] (II) Nano-silicon deposition

[0149] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 530° C. under nitrogen protection. Disilane with a volume concentration of 8% was introduced, and chemical vapor deposition was performed for 1 hour to obtain a silicon-carbon core.

[0150] (III) Carbon coating

[0151] The silicon-carbon core and 200 g of acetone were mixed evenly, placed in an atmosphere furnace under a nitrogen atmosphere, heated to 750°C at a heating rate of 3°C / min, and carbon coated for 4.0 h. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000 r / min, passed through a 500-mesh sieve, and demagnetized.

[0152] Example 6

[0153] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0154] (I) Preparation of silicon carbon matrix

[0155] Crystalline silicon (Dv50 of 80 nm and weight of 450 g), phenolic resin, ammonium carbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 1:3.5:0.3:0.08:14 for VC mixing for 2 h at a mixing speed of 1500 rpm to prepare a slurry. The slurry was spray dried (inlet air temperature of 180°C and outlet air temperature of 90°C) and then carbonized at 850°C for 6 h in an argon atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix were tested.

[0156] (II) Nano-silicon deposition

[0157] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the reactor was heated to 500°C under argon protection. Monosilane with a volume concentration of 10% was introduced, and chemical vapor deposition was performed for 4.5 hours to obtain a silicon-carbon core.

[0158] (III) Carbon coating

[0159] Under argon atmosphere, the silicon-carbon core was placed in an atmosphere furnace, heated to 700°C at a heating rate of 5°C / min, and acetylene with a volume concentration of 20% was introduced for 2.0h of carbon coating. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0160] Example 7

[0161] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0162] (I) Preparation of silicon carbon matrix

[0163] Crystalline silicon (Dv50 of 80 nm and weight of 450 g), phenolic resin, ammonium carbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 1:5.0:0.4:0.08:16 for VC mixing for 2 h at a mixing speed of 1500 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 180°C and outlet air temperature of 90°C) and then carbonized at 850°C for 6 h in an argon atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix were tested.

[0164] (II) Nano-silicon deposition

[0165] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 500° C. under argon protection. Monosilane with a volume concentration of 15% was introduced, and chemical vapor deposition was performed for 5 hours to obtain a silicon-carbon core.

[0166] (III) Carbon coating

[0167] Under argon atmosphere, the silicon-carbon core was placed in an atmosphere furnace, heated to 750°C at a heating rate of 5°C / min, and propane with a volume concentration of 20% was introduced for carbon coating for 2.0 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0168] Example 8

[0169] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0170] (I) Preparation of silicon carbon matrix

[0171] Crystalline silicon (Dv50 of 80 nm and weight of 450 g), phenolic resin, ammonium carbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 1:8.0:0.44:0.05:20 for 4 hours at a mixing speed of 1000 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 180°C and outlet air temperature of 90°C) and then carbonized at 850°C for 6 hours in an argon atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix were tested.

[0172] (II) Nano-silicon deposition

[0173] 1200 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 550° C. under argon protection. Monosilane with a volume concentration of 20% was introduced, and chemical vapor deposition was performed for 5 hours to obtain a silicon-carbon core.

[0174] (III) Carbon coating

[0175] The silicon-carbon core and 180 g of toluene were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 800°C at a heating rate of 5°C / min, and carbon coated for 4.0 hours to obtain a silicon-carbon composite material. It was then broken up at a speed of 1000 r / min, passed through a 500-mesh sieve, and demagnetized.

[0176] Example 9

[0177] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0178] (I) Preparation of silicon carbon matrix

[0179] Crystalline silicon (Dv50 of 80 nm and weight of 500 g), phenolic resin, ammonium bicarbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 1:2.5:0.25:0.05:9 for VC mixing for 2 h at a mixing speed of 1500 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 180°C and outlet air temperature of 90°C) and carbonized at 850°C for 6 h in an argon atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix were tested.

[0180] (II) Nano-silicon deposition

[0181] 1500 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 550° C. under argon protection. Disilane with a volume concentration of 12.5% ​​was introduced, and chemical vapor deposition was performed for 2 hours to obtain a silicon-carbon core.

[0182] (III) Carbon coating

[0183] The silicon-carbon core and 210 g of polyaniline were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 850°C at a heating rate of 5°C / min, and carbon coated for 4.0 hours to obtain a silicon-carbon composite material, which was then broken up at a speed of 1200 r / min, passed through a 500-mesh sieve, and demagnetized.

[0184] Example 10

[0185] This embodiment is a method for preparing a silicon-carbon composite material, which includes the following steps.

[0186] (I) Preparation of silicon carbon matrix

[0187] Crystalline silicon (Dv50 is 120nm, weight is 500g), phenolic resin, ammonium bicarbonate, polyethylene glycol and ethanol are mixed in a mass ratio of 1:13.2:0.42:0.05:24 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray dried (inlet air temperature is 180℃, outlet air temperature is 90℃), and then carbonized at 900℃ for 6h in an argon atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix are tested.

[0188] (II) Nano-silicon deposition

[0189] 1500 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 550°C under argon protection. Disilane with a volume concentration of 20% was introduced, and chemical vapor deposition was performed for 4.5 hours to obtain a silicon-carbon core.

[0190] (III) Carbon coating

[0191] The silicon-carbon core and 360 g of glucose were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 850°C at a heating rate of 7.5°C / min, and carbon coated for 4.0 h. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000 r / min, passed through a 500-mesh sieve, and demagnetized.

[0192] Comparative Example 1

[0193] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0194] (I) Preparation of silicon carbon matrix

[0195] Crystalline silicon (Dv50 of 80 nm and weight of 500 g), asphalt, ammonium carbonate, sodium dodecyl sulfate and n-hexane were mixed in a mass ratio of 1:1.2:0.10:0.03:5.4 for VC mixing for 2 h at a mixing speed of 1500 rpm to prepare a slurry. The slurry was spray-dried (inlet air temperature of 170°C and outlet air temperature of 80°C) and carbonized at 750°C for 5 h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix were tested.

[0196] (II) Carbon coating

[0197] Under a nitrogen atmosphere, the silicon-carbon matrix obtained in step (I) is placed in an atmosphere furnace, heated to 700°C at a heating rate of 3°C / min, and acetylene with a volume concentration of 15% is introduced for carbon coating for 1.5 hours. After obtaining the silicon-carbon composite material, it is broken up at a speed of 1000 r / min, passed through a 500-mesh sieve and demagnetized.

[0198] Comparative Example 2

[0199] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0200] (I) Preparation of silicon carbon matrix

[0201] Crystalline silicon (Dv50 of 80 nm and weight of 500 g), asphalt, sodium dodecyl sulfate and n-hexane were mixed in a mass ratio of 1:3.6:0.03:10 for VC mixing at a mixing speed of 1500 rpm for 2 hours to prepare a slurry. The slurry was spray-dried (inlet air temperature of 170°C and outlet air temperature of 80°C) and carbonized at 750°C for 5 hours in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix were tested.

[0202] (II) Nano-silicon deposition

[0203] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 500°C under nitrogen protection, introduce monosilane with a volume concentration of 20%, and perform chemical vapor deposition for 3 hours to obtain a silicon-carbon core.

[0204] (III) Carbon coating

[0205] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 700°C at a heating rate of 3°C / min. Acetylene with a volume concentration of 15% was introduced and carbon coating was carried out for 1.5 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0206] Comparative Example 3

[0207] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0208] (I) Preparation of silicon carbon matrix

[0209] Crystalline silicon (Dv50 is 80nm, weight is 500g), asphalt, ammonium carbonate, sodium dodecyl sulfate and n-hexane are mixed in a mass ratio of 1:3.6:0.6:0.03:10 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray-dried (inlet air temperature is 170℃, outlet air temperature is 80℃), and then carbonized at 750℃ for 5h in a nitrogen atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix are tested.

[0210] (II) Nano-silicon deposition

[0211] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 500°C under nitrogen protection, introduce monosilane with a volume concentration of 20%, and perform chemical vapor deposition for 3 hours to obtain a silicon-carbon core.

[0212] (III) Carbon coating

[0213] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace and heated to 700°C at a heating rate of 3°C / min. Acetylene with a volume concentration of 15% was introduced and carbon coating was carried out for 1.5 hours. After obtaining the silicon-carbon composite material, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve and demagnetized.

[0214] Comparative Example 4

[0215] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0216] (I) Preparation of silicon carbon matrix

[0217] Crystalline silicon (Dv50 is 80nm, weight is 500g), asphalt, ammonium carbonate, sodium dodecyl sulfate and n-hexane are mixed in a mass ratio of 1:3.6:0.3:0.03:10 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray-dried (inlet air temperature is 170℃, outlet air temperature is 80℃), and then carbonized at 750℃ for 5h in a nitrogen atmosphere to obtain a silicon-carbon matrix, and the physical properties and chemical composition of the silicon-carbon matrix are tested.

[0218] (II) Nano-silicon deposition

[0219] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 500°C under nitrogen protection, introduce monosilane with a volume concentration of 20%, and perform chemical vapor deposition for 3 hours to obtain a silicon-carbon core.

[0220] (III) Carbon coating

[0221] Under a nitrogen atmosphere, the silicon-carbon core was placed in an atmosphere furnace, heated to 700°C at a heating rate of 3°C / min, acetylene with a volume concentration of 15% was introduced, and carbon coating was carried out for 1.5 hours. Then, it was placed in an atmosphere furnace under nitrogen protection, heated to 1000°C, kept warm for 4 hours, and annealed to convert the amorphous silicon of the nano-silicon into crystalline silicon. After cooling to room temperature, it was broken up at a speed of 1000r / min, passed through a 500-mesh sieve, and demagnetized.

[0222] The results of XRD test of the silicon-carbon composite material of Comparative Example 4 are as follows: Figure 4 As shown, the XRD spectrum only contains the diffraction peaks of crystalline silicon, indicating that the nano-silicon in Comparative Example 4 is converted from amorphous silicon to crystalline silicon after the annealing process.

[0223] Comparative Example 5

[0224] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0225] (I) Preparation of carbon matrix

[0226] Phenolic resin, ammonium carbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 8.0:0.44:0.05:20 for 4 hours at a mixing speed of 1000 rpm to prepare a slurry. The slurry was spray dried (inlet air temperature was 180°C, outlet air temperature was 90°C), and then carbonized at 850°C for 6 hours in an argon atmosphere to obtain a carbon matrix. The physical properties and chemical composition of the carbon matrix were tested.

[0227] (II) Nano-silicon deposition

[0228] 1200 g of the carbon substrate was placed in a vapor deposition reactor, the air was removed until the oxygen content was less than 50 ppm, and the reaction mixture was heated to 550° C. under argon protection. Monosilane with a volume concentration of 20% was introduced, and chemical vapor deposition was performed for 5 hours to obtain a silicon-carbon core.

[0229] (III) Carbon coating

[0230] The silicon-carbon core and 180 g of toluene were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 800°C at a heating rate of 5°C / min, and carbon coated for 4.0 hours to obtain a silicon-carbon composite material. It was then broken up at a speed of 1000 r / min, passed through a 500-mesh sieve, and demagnetized.

[0231] The results of XRD test of the silicon-carbon composite material of Comparative Example 5 are as follows: Figure 5 As shown, the XRD spectrum only contains the diffraction peak of silicon carbide, and no diffraction peak of silicon, which indicates that the nano-silicon deposited in Comparative Example 5 reacts with carbon to generate silicon carbide after being coated with high-temperature carbon.

[0232] Comparative Example 6

[0233] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0234] (I) Preparation of silicon carbon matrix

[0235] Crystalline silicon (Dv50 is 150nm, weight is 500g), phenolic resin, ammonium bicarbonate, polyethylene glycol and ethanol are mixed in a mass ratio of 1:2.5:0.25:0.05:9 for VC mixing for 2h at a mixing speed of 1500rpm to prepare a slurry. The slurry is spray dried (inlet air temperature is 180℃, outlet air temperature is 90℃), and then carbonized at 850℃ for 6h in an argon atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix are tested.

[0236] (II) Nano-silicon deposition

[0237] 1500 g of silicon-carbon substrate was placed in a vapor deposition reactor, air was removed until the oxygen content was less than 50 ppm, and the substrate was heated to 550° C. under argon protection. Disilane with a volume concentration of 12.5% ​​was introduced, and chemical vapor deposition was performed for 2 hours to obtain a silicon-carbon core.

[0238] (III) Carbon coating

[0239] The silicon-carbon core and 210 g of polyaniline were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 850°C at a heating rate of 5°C / min, and carbon coated for 4.0 hours to obtain a silicon-carbon composite material, which was then broken up at a speed of 1200 r / min, passed through a 500-mesh sieve, and demagnetized.

[0240] Comparative Example 7

[0241] This comparative example is a method for preparing a silicon-carbon composite material, which comprises the following steps.

[0242] (I) Preparation of silicon carbon matrix

[0243] Crystalline silicon (Dv50 of 80 nm and weight of 450 g), phenolic resin, ammonium carbonate, polyethylene glycol and ethanol were mixed in a mass ratio of 1:13.5:0.48:0.08:28 for 4 hours at a mixing speed of 1000 rpm to prepare a slurry. The slurry was spray dried (inlet air temperature of 180°C and outlet air temperature of 90°C) and then carbonized at 850°C for 6 hours in an argon atmosphere to obtain a silicon-carbon matrix. The physical properties and chemical composition of the silicon-carbon matrix were tested.

[0244] (II) Nano-silicon deposition

[0245] Take 1000g of silicon-carbon substrate and place it in a vapor deposition reactor, exclude air until the oxygen content is less than 50ppm, heat to 550°C under nitrogen protection, introduce monosilane with a volume concentration of 25%, and perform chemical vapor deposition for 6.5h to obtain a silicon-carbon core.

[0246] (III) Carbon coating

[0247] The silicon-carbon core and 180 g of toluene were mixed evenly, placed in an atmosphere furnace under an argon atmosphere, heated to 800°C at a heating rate of 5°C / min, and carbon coated for 4.0 hours to obtain a silicon-carbon composite material. It was then broken up at a speed of 1000 r / min, passed through a 500-mesh sieve, and demagnetized.

[0248] The physical properties and chemical composition test results of the silicon-carbon matrix or carbon matrix obtained in Examples 1 to 10 and Comparative Examples 1 to 7 are shown in Table 1. The physical properties and chemical composition tests of the silicon-carbon composite materials obtained in Examples 1 to 10 and Comparative Examples 1 to 7 are shown in Table 2. The silicon-carbon composite materials obtained in Examples 1 to 10 and Comparative Examples 1 to 7 are made into button cells for electrochemical performance tests. The button cell preparation process and test conditions are as follows, and the test results are shown in Table 3.

[0249] The test conditions are described below.

[0250] (1) Physical properties test

[0251] The grain size of nano-silicon in silicon-carbon composite materials was tested using high-resolution transmission electron microscopy.

[0252] The particle size distribution was obtained by laser particle size analyzer.

[0253] The tap density is obtained by using a tap density meter.

[0254] The true density is obtained by testing with a true density meter.

[0255] The specific surface area, average pore size, pore volume and pore size distribution curve were obtained by nitrogen isothermal adsorption and desorption curve test. Among them, the ratio of the pore volume of the silicon carbon matrix with a pore size of 1nm to 10nm to the total pore volume is P, and the pore volume within 1nm to 10nm is obtained from the pore size distribution curve.

[0256] The thickness of the carbon coating was measured using high-resolution transmission electron microscopy.

[0257] X-ray diffractometer was used to test the phase analysis of silicon-carbon composite materials.

[0258] The cross-sectional transmission spectrum of the silicon-carbon composite material was obtained by combining the focused ion beam technology and the transmission electron microscope. Any cross section of the silicon-carbon composite material in the spectrum was selected as region 1, any cross section was selected as region 2, the median particle size Dv50 of the crystalline silicon was recorded as d, and the cross-sectional area of ​​region 1 and region 2 was 100d 2 and 400d 2 The ratio of the number of nano-silicon particles to the number of crystalline silicon particles in region 1 is recorded as α1, and the ratio of the number of nano-silicon particles to the number of crystalline silicon particles in region 2 is recorded as α2. The distribution uniformity of the nano-silicon particles and the crystalline silicon particles can be represented by the fluctuation value of the particle number ratio α1 / α2. The number of nano-silicon particles and the number of crystalline silicon in region 1 and region 2 can be directly statistically obtained. The particle region where the nano-silicon particles are located has no obvious lattice fringes, and the particle region where the crystalline silicon is located has obvious lattice fringes. Finally, the fluctuation value of the particle number ratio α1 / α2 is calculated.

[0259] (2) Chemical composition test

[0260] The carbon content was obtained by using a carbon-sulfur analyzer.

[0261] The silicon content was measured by inductively coupled plasma atomic emission spectrometry.

[0262] Among them, the mass ratio of nano-silicon to crystalline silicon is R. The calculation method of R is: the carbon content and silicon content of the silicon-carbon matrix are measured to be A1 and B1 respectively; the carbon content and silicon content of the silicon-carbon core are measured to be A2 and B2 respectively, and the calculation formula of the mass ratio of nano-silicon to crystalline silicon R is: R = (A1B2-A2B1) / A2B1

[0263] (3) Electrochemical performance test

[0264] The silicon-carbon composite materials of Examples 1 to 10 and Comparative Examples 1 to 7 were respectively used as active materials, mixed with a water dispersion of a binder acrylonitrile multipolymer (LA132, solid content 15%) and a conductive agent (Super-P) in a mass ratio of 92:6:2, and an appropriate amount of water was added as a solvent to adjust the solid content of the slurry to 55%, coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. A metal lithium sheet was used as a counter electrode, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v / v) were used to form an electrolyte, a polypropylene microporous membrane was used as a diaphragm, and a CR2032 button cell was assembled in a glove box filled with inert gas. The charge and discharge test of the button cell was carried out on the LANHE battery test system of Landian Electronics Co., Ltd.

[0265] The first charge and discharge performance test: At room temperature, discharge at a constant current of 0.1C to a voltage of 0.01V, then discharge at a constant current of 0.02C to a voltage of 0.005V, and charge at a constant current of 0.1C to a voltage of 1.5V to obtain the first reversible specific capacity and the first coulombic efficiency.

[0266] Rate performance test: Under room temperature conditions, cycle at a current of 0.1C for 5 weeks, then cycle at a current of 0.2C for 5 weeks, cycle at a current of 0.5C for 5 weeks, cycle at a current of 1C for 5 weeks, cycle at a current of 2C for 5 weeks, and finally cycle at a current of 0.1C for 5 weeks.

[0267] Cyclic performance test: Under normal temperature conditions, 1C constant current charge and discharge to 0.01V, then 0.05C constant current discharge to 0.005V, and finally 1C constant current charge to 1.5V to obtain the de-lithiation specific capacity. This cycle is repeated 300 times, and the capacity retention rate after 300 cycles is calculated. The 300-week capacity retention rate is the ratio of the de-lithiation specific capacity in the 300th week to the de-lithiation specific capacity in the first week.

[0268] Table 1 Physical properties and chemical composition of silicon carbon matrix or carbon matrix obtained in Examples 1 to 10 and Comparative Examples 1 to 7

[0269]

[0270]

[0271] Table 2 Physical properties and chemical composition of silicon-carbon composite materials obtained in Examples 1 to 10 and Comparative Examples 1 to 7

[0272]

[0273] Table 3 Electrochemical properties of silicon-carbon composite materials obtained from Examples 1 to 10 and Comparative Examples 1 to 7

[0274]

[0275]

[0276] From the results of Tables 1 to 2, it can be seen that the silicon-carbon composite material of the present invention has better physical properties. At the same time, the ratio P of the pore volume of the silicon-carbon matrix with a pore diameter of 1nm to 10nm to the total pore volume is between 0.4 and 0.8. At this P value, there is sufficient pore capacity for nano-silicon and the stability of the material structure can be maintained. The mass ratio R of nano-silicon to crystalline silicon is between 0.2 and 20.0, and the silicon-carbon composite material has better electrochemical properties. The distribution uniformity of nano-silicon and crystalline silicon α1 / α2 is between 0.67 and 1.50, indicating that the nano-silicon and crystalline silicon are evenly distributed in the silicon-carbon composite material. Combined with the results of Table 3, it can also be seen that the silicon-carbon composite material of the present invention has better electrochemical properties.

[0277] It can be seen from Examples 1 to 10 and Comparative Example 1 that nano-silicon is deposited in the pores of the silicon-carbon matrix through the chemical vapor deposition process, and the nano-silicon and the crystalline silicon in the silicon-carbon skeleton have a uniform distribution, which is beneficial to improving the expansion of the material and enhancing the cycle performance of the silicon-carbon composite material. At the same time, the specific surface area of ​​the material after nano-silicon filling is lower, which is beneficial to the improvement of the first coulomb efficiency.

[0278] It can be seen from Examples 1 to 10 and Comparative Example 2 that no pore-forming agent is added during the preparation of the silicon-carbon matrix, the skeleton pore volume is small, and after chemical vapor deposition, most of the nanosilicon is distributed on the surface of the material, affecting the electrical conductivity. At the same time, the nanosilicon and crystalline silicon particles are unevenly distributed (α1 / α2 is outside the range of 0.67 to 1.50), resulting in poor rate performance and cycle performance of the material.

[0279] It can be seen from Examples 1 to 10 and Comparative Example 3 that excessive pore-forming agent is added during the preparation of the silicon-carbon matrix, the P value is too small, only 0.35, and after silicon vapor deposition, nano-silicon and crystalline silicon are unevenly distributed (α1 / α2 is outside the range of 0.67 to 1.50), and the specific surface area of ​​the material is large, resulting in a low first coulomb efficiency, and poor rate performance and cycle performance.

[0280] It can be seen from Examples 1 to 10 and Comparative Example 4 that after the nano-silicon is deposited, it is subjected to high-temperature annealing treatment and is completely converted from amorphous silicon to crystalline silicon. That is, the silicon-carbon composite material of Comparative Example 4 contains only crystalline silicon, and the crystalline silicon is distributed in the skeleton and pores of the silicon-carbon matrix, which produces a large volume expansion during the charge and discharge process, thereby resulting in poor material cycle performance.

[0281] It can be seen from Example 8 and Comparative Example 5 that crystalline silicon is not added during the preparation of the silicon-carbon matrix, that is, nano-silicon is deposited on the porous carbon skeleton. During the nano-silicon deposition and subsequent high-temperature carbon coating process, nano-silicon is more likely to react with the porous carbon skeleton or the second carbon source in the coating process to generate silicon carbide, which leads to the reversible specific capacity, coulombic efficiency, rate performance and cycle performance of the silicon-carbon composite material of Comparative Example 5 being poor.

[0282] It can be seen from Example 9 and Comparative Example 6 that if the Dv50 of the crystalline silicon added during the preparation of the silicon-carbon matrix is ​​large, it will cause severe expansion during the charge and discharge process, thereby affecting the cycle performance of the silicon-carbon composite material and resulting in a low capacity retention rate.

[0283] For Example 8 and Comparative Example 7, it can be seen that if the crystalline silicon content in the silicon-carbon matrix is ​​low, and a high content of nano-silicon is deposited in the pores of the silicon-carbon matrix by chemical vapor deposition, resulting in R of 22.6, it will not be possible to ensure that the nano-silicon remains amorphous after high-temperature carbon coating and that no silicon carbide is generated during the reaction. Due to the high silicon content, although the silicon-carbon composite material has a high capacity, the first coulomb efficiency is low, and the rate performance and cycle performance are poor.

[0284] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that: It includes a silicon-carbon core and a carbon coating layer coating the silicon-carbon core, the silicon-carbon core includes a silicon-carbon matrix and nano-silicon, the silicon-carbon matrix includes a silicon-carbon skeleton composited with crystalline silicon and carbon materials and a plurality of holes penetrating the silicon-carbon skeleton, the nano-silicon is accommodated in the plurality of holes, the ratio of the pore volume of the silicon-carbon matrix with a pore diameter of 1nm to 10nm to the total pore volume is P, 0.4≤P≤0.8, the distribution uniformity of the nano-silicon and the crystalline silicon is α1 / α2, 0.67≤α1 / α2≤1.

50.

2. The silicon-carbon composite material according to claim 1, characterized in that: Contains at least one of the following features ① to ⑥: ① The tap density of the silicon-carbon composite material is 0.6 g / cm 3 Up to 1.5g / cm 3 ; ② The true density of the silicon-carbon composite material is 1.5 g / cm 3 Up to 2.0g / cm 3 ; ③The pore volume of the silicon-carbon composite material is 0.001cm 3 / g to 0.100cm 3 / g; ④ The specific surface area of ​​the silicon-carbon composite material is 1m 2 / g to 10m 2 / g; ⑤ The median particle size of the silicon-carbon composite material is 1 μm to 50 μm; ⑥ The mass content of silicon in the silicon-carbon composite material is 30% to 75%.

3. The silicon-carbon composite material according to claim 1, characterized in that: Contains at least one of the following features (1) to (17): (1) The true density of the silicon carbon matrix is ​​1.5 g / cm 3 Up to 2.4g / cm 3 ; (2) The pore volume of the silicon carbon matrix is ​​0.1 cm 3 / g to 0.8cm 3 / g; (3) The specific surface area of ​​the silicon carbon matrix is ​​200 m 2 / g to 1800m 2 / g; (4) The Dv50 of the silicon carbon matrix is ​​1 μm to 40 μm; (5) The average pore size of the pores is 1 nm to 100 nm; (6) The pores include at least one of micropores, mesopores and macropores; (7) The Dv50 of the crystalline silicon is 50 nm to 120 nm; (8) The particle size distribution dispersion of the crystalline silicon is σ, 0<σ≤1.0, σ=(Dv90-Dv10) / Dv50; (9) The crystalline silicon accounts for 10% to 60% of the mass of the silicon-carbon matrix; (10) The carbon material comprises soft carbon and / or hard carbon; (11) The nano-silicon is amorphous silicon, and the grain size of the amorphous silicon is ≤3nm; (12) The mass ratio of the nano-silicon to the crystalline silicon is R, 0.2≤R≤20.0; (13) The nano-silicon accounts for 10% to 75% of the total mass of the silicon-carbon composite material; (14) The nano-silicon is also distributed on the surface of the silicon-carbon matrix; (15) The thickness of the carbon coating layer is 2 nm to 200 nm; (16) The carbon coating layer accounts for 1% to 15% of the mass of the silicon-carbon composite material; (17) The carbon coating layer includes crystalline carbon and / or amorphous carbon.

4. A method for preparing a silicon-carbon composite material, characterized in that: Includes steps: (I) Preparation of silicon carbon matrix Mixing crystalline silicon, a first carbon source, a pore former and a dispersant in a solvent to obtain a slurry, drying the slurry and then carbonizing it to obtain a silicon-carbon matrix, wherein the pore former forms pores in the silicon-carbon matrix after carbonization, and the ratio of the pore volume of the silicon-carbon matrix with a pore diameter of 1 nm to 10 nm to the total pore volume is P, 0.4≤P≤0.8, the Dv50 of the crystalline silicon is 50 nm to 120 nm, and the mass ratio of the crystalline silicon, the first carbon source, the pore former, the dispersant and the solvent is 1:0.2-15.0:0.05-0.50:0.03-0.30:1-30; (II) Nano-silicon deposition Depositing nano-silicon on the silicon-carbon matrix, so that the nano-silicon is at least deposited in the pores to obtain a silicon-carbon core, wherein the mass ratio of the nano-silicon to the crystalline silicon in the silicon-carbon core is R, 0.2≤R≤20.0; (III) Carbon coating The silicon-carbon core is carbon-coated with a second carbon source.

5. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The nano-silicon deposition on the silicon-carbon substrate comprises introducing a gaseous silicon source into a reactor containing the silicon-carbon substrate under a protective gas to perform vapor phase deposition.

6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: Contains at least one of the following features (i) to (vi): (i) the protective gas comprises at least one of nitrogen, helium, neon, argon, krypton and xenon; (ii) the gaseous silicon source is obtained by heating a silicon source material at 40° C. to 200° C., the silicon source material is in a liquid phase and includes at least one of trisilane, butadisilane, trichlorosilane, methyltrichlorosilane and dimethyldichlorosilane; (iii) the gaseous silicon source is at least one of monosilane, disilane, monochlorosilane and dichlorosilane; (iv) the volume concentration of the gaseous silicon source is 5% to 50%; (v) the vapor deposition temperature is 400° C. to 700° C.; (vi) The vapor deposition time is 1 hour to 12 hours.

7. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: Contains at least one of the following features (i) to (ii): (i) the particle size distribution dispersion σ of the crystalline silicon, 0<σ≤1.0, σ=(Dv90-Dv10) / Dv50; (ii) the first carbon source comprises at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin and citric acid; (iii) the pore-forming agent comprises at least one of ammonium carbonate, ammonium bicarbonate, magnesium carbonate, magnesium bicarbonate, ammonium oxalate, ammonium phosphate, diammonium hydrogen phosphate and ammonium nitrate; (iv) the dispersant comprises at least one of sodium lauryl sulfate, polyacrylamide, polyethylene glycol fatty acid esters, polyvinyl pyrrolidone, stearic acid monoglyceride and polyethylene glycol; (5) the solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane and cyclohexane; (vi) the mixing is grinding mixing, ball milling mixing or VC mixing; (VII) The mixing time is 1 hour to 5 hours; (VIII) the mixing speed is 500 rpm to 2500 rpm; (IX) The drying is spray drying, the feed inlet temperature of the spray drying is 150°C to 280°C, and the discharge outlet temperature of the spray drying is 70°C to 150°C; (j) the carbonization is carried out in a protective gas, wherein the protective gas is at least one of nitrogen, helium, neon, argon, krypton and xenon; (XI) The carbonization temperature is 600°C to 1000°C; (XII) The carbonization time is 1 hour to 10 hours.

8. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The carbon coating comprises mixing the silicon-carbon core and the second carbon source under a protective gas and performing a high-temperature heat treatment.

9. The method for preparing the silicon-carbon composite material according to claim 8, characterized in that: Contains at least one of the following features (a) to (l): (a) the protective gas comprises at least one of nitrogen, helium, neon, argon, krypton and xenon; (b) the second carbon source is at least one of a gaseous carbon source, a liquid carbon source and a solid carbon source; (c) the second carbon source is a gaseous carbon source, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene and acetylene; (d) the second carbon source is a gas phase carbon source, and the step of mixing the gas phase carbon source and the silicon carbon core comprises: heating the silicon carbon core and then introducing the gas phase carbon source; (e) the second carbon source is a gaseous carbon source, and the volume concentration of the gaseous carbon source is 5% to 50%; (f) the second carbon source is a liquid carbon source, and the liquid carbon source is at least one of n-hexane, cyclohexane, isoheptane, acetone, butanone, cyclohexanone, benzene, toluene, xylene, styrene, phenol, methyl acetate, ethyl acetate, propyl acetate and liquefied petroleum gas; (g) the second carbon source is a liquid carbon source, and the mass ratio of the liquid carbon source to the silicon-carbon core is 1:2 to 50; (h) the second carbon source is a solid carbon source, and the solid carbon source includes at least one of asphalt, phenolic resin, epoxy resin, polyvinyl alcohol, polypyrrole, polyaniline, polydopamine, sucrose, glucose, citric acid and lignin; (i) the second carbon source is a solid carbon source, and the mass ratio of the solid carbon source to the silicon-carbon core is 1:2-50; (j) the temperature of the heat treatment is 600° C. to 900° C.; (k) the heat treatment time is 1 hour to 12 hours; (l) After the heat treatment, the particles are then broken up, screened and demagnetized.

10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the silicon-carbon composite material described in any one of claims 1 to 3 or the silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Porous silicon carbon-based composite material and preparation method thereof, negative electrode and lithium ion battery

    CN116779816A